Investigation on solar water heater with different types of turbulators. (2021) - Vasanthaseelan, S.; Manoj Kumar, P.; Anandkumar, R.; Hari Ram, K.; Subbiah, Ram; Suresh, V.; Abishek, A.S.; Anith, R.; Aravinth, P.; Balaji, S.V.
Abstract: Solar water heaters have become unavoidable renewable energy systems for the most of the residential, commercial and industrial hot water requirements. Evacuated tube collector (ETC) based solar water heaters are widely used for the aforementioned purposes in recent days due to their relative advantages over other systems. Exclusively, the ETC systems are very economical and efficient for the passive operation. Hence, they are keenly installed in the commercial and residential buildings. A major hiccup with ETC systems in passive mode of operation is the poor water circulation at the lower end of the ETCs, which make them inactive in most of the time and reduces the effective absorber area. This work is planned to curtail the aforementioned issue of the ETCs by inducing turbulence using two different types of turbulators, namely coiled turbulator and matrix turbulator inside the ETC. The experiments were accomplished in three modes namely, ETC without turbulator (Simple-ETC), ETC with coiled turbulator (CT-ETC) and ETC with matrix turbulator (MT-ETC). The results were compared and analyzed. The major results revealed that the presence of the turbulators significantly enhanced the ETC tube mean temperature by stimulating turbulence. They simultaneously improved the solar gain and thereby, mean tank water temperature was boosted-up. Quantitatively, the tank water temperature was escalated by 3.5 °C and 7.5 °C, with the aid of coiled turbulator and matrix turbulator, respectively. Further, the matrix turbulator seems ahead in improving heat transfer inside the ETC compared to coiled turbulator.